Cornual pregnancy post salpingectomy: report of an unusual case - Tang, Luis (2015)
Ectopic pregnancy is a pathology often encountered in the gynecologist practice. It is possible to have diverse extra-uterine implantation sites, some of them unsuspected. A case of cornual (stump) ectopic pregnancy with absent tube due to salpingectomy performed a year earlier for ectopic pregnancy and evidence of ovulation from the contra-lateral ovary (evidence of corpus luteum) and tube intact, corresponding to abdominal pregnancy, is presented. Resection of trophoblast was performed by laparoscopy, thus corroborating the anatomic and pathologic diagnosis of ectopic pregnancy. Postoperative outcome was satisfactory.